Studi Populasi Dan Habitat Anoa (Bubalus sp) di Kawasan Hutan Lindung Desa Sangginora Kabupaten Poso - Reza Ariawan Ranuntu; Sri Ningsih Mallombasang (Universitas Tadulako, 2015)
The research objective is to estimate and study the genaral picture of dwarf buffalo (Bubalus sp) in oder that their presence around can still be recorded and better managed in Sulawesi. Descriptive research method was used by applying line transect to observe population quadrat transect was used to analyze habitat composition. Based on footprints found, there were estimated that were about less that 12 adult, 8 teenagers and 5 young dwarf buffaloes around within 13 obrvation points with density of 1.23 dwarf buffaloes/km2 or around 1 – 2 per square kilometres. For habitat vegetaton, there were about 85 species function as supporting habitat and about 33 species as food sources. Laboratory analysis noted that soil texture on the sites are clay with salinity level of 0.72 µS/cm. In addition, it was recorded that the temperature during the morning time were about 140 C – 180 C, 180 C – 200 C during the noon time, and arond 200 C – 150 C during the evening time. To summarize, the population sze of dwarf buffalo can be conculded as low leading to extinction if illegal hunting and habitat destruction continuously occur.